(3GdCQHYhf Ydi ePgH GdeJMbbjf ef GdeJUhaIs - (3GdMGaX CHj fYje CMeO Hf YHO Gddg Hf CMeO GdCUagGfj,J (B430 (3g` s ((3GdSjO GdMSf Hf GdMSjf Hf YR GdOjf Hf GdMSf GdTGei GdOGYi GdgGOhi s)
(3ChdgG (B:s
(3CeG HYO aEfi CMHHJ Cf CLeY ai eHGfi ePGgH GdeJUhaI hNdGFbge CMGOjK JThb GdfGXQ ajgG Edi EYJbGO eG cGf Ydjg ChGFdge ef GdeMbbjf s
(3BNQgG (B:s
(3gPG BNQ eG LeYI GdTjN CHh fYje ef CMhGd GdeMbbjf hGdMeO ddg Mb MeOg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B22 - (3U(B28s
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCMbGa eLehYI MSjf Hf Sgd (B((3eLGejY (B- (3JQje (B303) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs